Comparative study of mandibular cortical index in orthopantomogram and bone mineral density of lumbar vertebrae in dual energy x-ray absorptiometry in postmenopausal females in North India. - Rati G; Puja C; Sunita K; Shashi M; Alok KC; Anurag (Department of Surgery, UKM Medical Centre, 2014)
Osteoporosis is a bone disorder which results in low bone mineral content leading to recurrent fractures commonly seen in females after menopause. Few studies have proposed the use of orthopantomogram as a diagnostic marker for osteoporosis as it is simple, quick, easy, inexpensive, non-invasive and widely used. Present study was undertaken to assess the efficacy of OPG to diagnose osteoporosis apropos bone densitometry (DEXA).The study comprised fifty post-menopausal females who were subjected to panoramic radiographs and DEXA. The visual analysis was done based on the radiographic appearance of the lower border of the mandible on the left side by two observers who were blinded about DEXA results. Intra/Inter-observer variability was ruled out by repeated analysis followed by comparison of different grades of MCI (Mandibular Cortical Index) and BMD (Bone Mineral density) statistically. Significant difference in three groups of mandibular cortical index of panoramic radiograph as interpreted by the two observers (p value < 0.05) was found. The intra-observer reproducibility of this index had moderate agreement (Kappa value of 0.35 & 0.31) and the inter-observer agreement of this index followed fair reproducibility (kappa value of 0.38 &0.32). There was significant correlation between results obtained by mandibular cortical index (MCI) and bone mineral density (BMD) of the lumbar vertebrae as determined by the dual energy x-ray absorptiometry implicating visual assessment of the OPG as an important screening tool for osteoporosis in postmenopausal females.